A universal method for rapid and large‐scale growth of layered crystals. (25th November 2020) - Chaturvedi, Apoorva; Chen, Bo; Zhang, Keke; He, Qiyuan; Nam, Gwang‐Hyeon; You, Lu; Lai, Zhuangchai; Tan, Chaoliang; Tran, Thu Ha; Liu, Guigao; Zhou, Jiadong; Liu, Zheng; et al.
Abstract: Layered van der Waals (vdW) materials, consisting of atomically thin layers, are of paramount importance in physics, chemistry, and materials science owing to their unique properties and various promising applications. However, their fast and large‐scale growth via a general approach is still a big challenge, severely limiting their practical implementations. Here, we report a universal method for rapid (~60 min) and large‐scale (gram scale) growth of phase‐pure, high‐crystalline layered vdW materials from their elementary powders via microwave plasma heating in sealed ampoules. This method can be used for growth of 30 compounds with different components (binary, ternary, and quaternary) and properties. The ferroelectric and transport properties of mechanically exfoliated flakes validate the high crystal quality of the grown materials. Our study provides a general strategy for the fast and large‐scale growth of layered vdW materials with appealing physiochemical properties, which could be used for various promising applications. Abstract : A universal method for rapid (~60 min) and large‐scale (gram scale) growth of phase‐pure, high‐crystalline layered van der Waals materials from their elementary powders via microwave plasma heating in sealed ampoules. This method has been used for the growth of 30 compounds with different components (binary, ternary, and quaternary) and properties.